Etnografi Komunikasi Orang Tua - Anak di Kampung Inggris - Riza Al fakhuriziah; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2016)
This research method used the study of communication ethnography with phenomenology approach. The result of the research stated that the communication pattern of parents and children in